2014
DOI: 10.1063/1.4894722
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of dielectric constant in transition metal doped ZnO nanocrystals

Abstract: A possibility to obtain room temperature ferromagnetism by transition metal doping of ZnO nanoparticles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, with a further increase in dopant amount to 12%, the dielectric constant decreases in the present work. A similar type of behavior is reported in literature where a sharp increase in dielectric constant occurs with the introduction of dopant ions into the host material and then a decrement in dielectric constant takes place after a certain concentration of dopant ions [40,41]. This might be due to the increased concentration of metallic ions leading to enhanced conductivity and decreased dielectric constant [40].…”
Section: Dielectric Measurementssupporting
confidence: 82%
“…However, with a further increase in dopant amount to 12%, the dielectric constant decreases in the present work. A similar type of behavior is reported in literature where a sharp increase in dielectric constant occurs with the introduction of dopant ions into the host material and then a decrement in dielectric constant takes place after a certain concentration of dopant ions [40,41]. This might be due to the increased concentration of metallic ions leading to enhanced conductivity and decreased dielectric constant [40].…”
Section: Dielectric Measurementssupporting
confidence: 82%
“…The 377-cm −1 peak is due to an E 1 (TO) mode. Also, the sharpest and the strongest peak at 437 cm −1 can be assigned E 2 (high) due to the high-frequency branch of E 2 mode of ZnO, which is the strongest and characteristic mode of wurtzite crystal structure [ 50 55 ]. Raman peak corresponding to the high-energy range observed between ≈1030 and 1190 cm −1 is assigned to the E 2 (LO) second-order polar mode [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent time also, a lot of work has been published on magnetic ground state of TM doped ZnO as DMSs system. 33 Although room temperature ferromagneticlike Zn 0.9 Fe 0.1 O sample also shows an enhancement of dielectric constant, however, the observed increase is only by approximately ten times from that of pure ZnO. We have observed that net interaction for Mn, Co, and Ni doped ZnO nanoparticles, prepared by chemical reaction technique, is antiferromagnetic like.…”
Section: Introductionmentioning
confidence: 63%
“…Chakraborti et al 19 reported room temperature ferromagnetism in (Co, Cu) codoped ZnO thin films prepared by pulse laser deposition technique. 33 Here, we should mention that ZnFeCoO nanoparticles exhibit an enhancement of dielectric constant by $400 times a) Electronic mail: saniitkgp2007@gmail.com from that of pure ZnO. [20][21][22][23][24][25][26][27] In our earlier work on TM (¼ Fe, Co, Mn, and Ni) doped ZnO nanoparticles, we carried out our study on single TM doped ZnO.…”
Section: Introductionmentioning
confidence: 99%